2008
DOI: 10.1270/jsbbs.58.401
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in fruiting and flower-ornamental Japanese apricot (Prunus mume) germplasms assessed by SSR markers

Abstract: The genetic diversity and relationships among 127 Japanese apricot (Prunus mume Siebold et Zucc.) germplasms, including 56 fruiting and 55 flower-ornamental cultivars derived from Japan, 8 germplasms from China, 7 germplasms from Taiwan and 1 germplasm from Thailand were assessed by SSR markers. Thirtynine out of 58 SSR markers developed from peach and apricot could produce one or two amplified fragments in Japanese apricot, suggesting transferability across species. Fourteen SSR markers showing clear amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…In comparison, 58 Asian pear cultivars were differentiated by nine SSR markers with a total of 133 putative alleles by Kimura et al (2002). Moreover, 111 Japanese apricot, 41 carnation, and 51 olive cultivars could be discriminated by 14, 13, and seven SSR loci, respectively (Díaz et al, 2006;Hayashi et al, 2008;Kimura et al, 2009); therefore, the remaining 43 SSR primer sets developed in this study might be useful for discrimination of a greater number of gentian cultivars. The allele numbers detected by SCAR markers based on intron length polymorphism of flavonoid bio- Table 5.…”
Section: Application Of Ssr Markers For Cultivar Identificationmentioning
confidence: 84%
See 2 more Smart Citations
“…In comparison, 58 Asian pear cultivars were differentiated by nine SSR markers with a total of 133 putative alleles by Kimura et al (2002). Moreover, 111 Japanese apricot, 41 carnation, and 51 olive cultivars could be discriminated by 14, 13, and seven SSR loci, respectively (Díaz et al, 2006;Hayashi et al, 2008;Kimura et al, 2009); therefore, the remaining 43 SSR primer sets developed in this study might be useful for discrimination of a greater number of gentian cultivars. The allele numbers detected by SCAR markers based on intron length polymorphism of flavonoid bio- Table 5.…”
Section: Application Of Ssr Markers For Cultivar Identificationmentioning
confidence: 84%
“…Thus, we attempted to develop SSR markers containing di-nucleotide repeats applicable to Japanese gentian. To isolate SSR loci from plants lacking genomic and cDNA sequence information, several protocols, such as the screening of a genomic library by SSR probes (Chiba et al, 2003;Suwabe et al, 2002), utilization of SSR markers from closed species (Hayashi et al, 2008;Shiran et al, 2007), construction of an SSR-enriched library (Díaz et al, 2006;Nunome et al, 2006), and sequencing of amplified ISSR fragments (Hayden et al, 2004;Lian et al, 2001Lian et al, , 2006, have been developed. Our preliminary experiments using suppression PCR (Lian et al, 2001) to isolate SSRs in Japanese gentian were inefficient, although the reason was not clearly understood (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However their study placed Hungarian cultivars closer to the Central Asian group than to the other European cultivars. Hayashi et al (2008) studied Japanese apricot (Prunus mume) germplasm and reported that the genetic diversity and relationships among 127 Japanese apricot germplasms assessed by SSR markers. Their study supported the two hypotheses that Japanese apricot cultivated in Japan had been introduced from China and that fruiting cultivars had been selected from flower-ornamentals.…”
Section: Genetic Diversity Of Apricot Based On Molecular Markersmentioning
confidence: 99%
“…Among the molecular markers available, microsatellites or simple sequence repeats (SSR), which are tandem repeats of 1-6 nucleotide long DNA motifs, have gained considerable importance in plant genetics and breeding because of their multi-allelic nature, codominant inheritance, high abundance, extensive genome coverage, reproducibility, and discriminatory power (Kalia et al, 2011). A variety of molecular marker techniques have been developed for measuring genetic variability/similarity in ornamental plants, such as random amplified polymorphic DNA (RAPD; Anthurium andraeanum and Chrysanthemum) (Nowbuth et al, 2005;Lapitan et al, 2007;Barakat et al, 2010), ISSR (Rose) (Jabbarzadeh et al, 2010), and SSR (Prunus mume and Nelumbonucifera) (Tian et al, 2008;Hayashi et al, 2008). Moreover, several molecular studies have employed various DNA markers in Curcuma spp.…”
Section: Introductionmentioning
confidence: 99%